أثر الإفصاح على قرارات المستثمرين في أسهم المصارف الإسلامية بالمملكة العربية السعودية - حمدان, عبدالله ناصر (Ma'ahad al-Masrafiyyah al-Islamiyah wa al-Tamwil, al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2013)
This study aims at identifying the effect of disclosure on investors' decisions in shares of Islamic banks in the Kingdom of Saudi Arabia through an analytical and field study, identifying characteristics of information available in the money market as well as determining the actual needs of investors for shares. The study adopted two approaches, the theoretical and practical. Through the use of the theoretical approach the study was able to identify the nature of disclosure, the influencing factors, their effect on financial crises, and the sources of information of investors. The current study utilized the practical approach, to identify the effect of disclosed information on investors' decisions in the shares of four Islamic banks, namely Al Rajhi Bank, Bank Al Jazira, Bank Albilad, Al Inma' Bank. The motives of investors' decision as well as the comprehensibility and understandability of the information have been demonstrated. The study concludes that there is inadequacy of investment awareness of share dealers and their dissatisfaction toward disclosing financial reports of participating companies, and that ethics and conducts influence the adequacy and quality of share markets. The study recommends that disclosure of financial reports in Islamic banks is dully emphasized.